Isolation and characterization of microvessel endothelial cells from human mammary adipose tissue - Hewett, P W; Murray, J C; Price, E A; Watts, M E; Woodcock, M (In vitro cellular & developmental biology. Animal, 1993)
A method for the isolation and long-term culture of human microvessel endothelial cells from mammary adipose tissue (HuMMEC) obtained at breast reduction surgery has been developed. Pure cultures of HuMMEC were isolated by sequential digestion of the fat with collagenase and trypsin followed by specific selection of microvessel fragments with Ulex europaeus agglutinin-1 coated magnetic beads (Dynabeads). The resulting cells formed contact-inhibited monolayers on gelatin and fibronectin substrates and capillary-like "tubes" on Matrigel; they also expressed von Willebrand factor, angiotensin-converting enzyme, and accumulated acetylated low density lipoprotein. Further immunofluorescence characterization revealed the presence of antigens for the endothelial cell specific monoclonal antibodies EN4 and H4-7/33. In addition, the origin of these cells was confirmed by the demonstration of the cell adhesion molecules, platelet endothelial cell adhesion molecule-1 (CD31), and endothelial leukocyte adhesion molecule-1 (ELAM-1/E-selectin) upon stimulation with tumor necrosis factor (TNF) alpha. HuMMEC were found to express-1 ELAM-1 at lower levels of TNF alpha (< 10 ng/ml) than required by human umbilical vein endothelial cells. These cells should provide a useful in vitro model for studying various aspects of microvascular biology and pathology.